2006
DOI: 10.1348/135910705x81000
|View full text |Cite
|
Sign up to set email alerts
|

Targets and dimensions of social comparison among people with spinal cord injury and other health problems

Abstract: The present research examined comparison targets and comparison dimensions among two Spanish samples of individuals facing serious illnesses and diseases. In Study 1, 90 older patients (mean age 66.36) with various age-related diseases, particularly cardiovascular diseases and diabetes, indicated that they compared themselves most often with others with the same disease, next with others with another disease and least with people without health problems. They compared themselves more often on their mental stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
29
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 36 publications
6
29
1
2
Order By: Relevance
“…This supports findings of Schulz and Decker (1985) and Buunk et al (2006aBuunk et al ( , 2006b, who also found ill and disabled participants to view themselves as better-off than those without disability.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This supports findings of Schulz and Decker (1985) and Buunk et al (2006aBuunk et al ( , 2006b, who also found ill and disabled participants to view themselves as better-off than those without disability.…”
Section: Discussionsupporting
confidence: 88%
“…The use of social comparison, where people compare themselves against others in order to judge how they are faring on a dimension, such as coping with an illness or rehabilitation after an injury, also influences adjustment. Previous research has shown this relationship of social comparison to adjustment in SCI (Buunk et al, 2006a(Buunk et al, , 2006bKennedy et al, 2003) and in other illnesses, such as cancer (Taylor et al, 1984) and Ménière's disease (Dibb and Yardley, 2006). …”
Section: Introductionmentioning
confidence: 79%
“…2 This significantly impacts the care and lifestyle of patients and also increases their risk to develop secondary health problems such as cardiovascular disease and diabetes. 3 Therefore, a major area of interest is the prevention or attenuation of muscle atrophy associated with SCI. Therapeutic interventions that focus on locomotor training have shown the potential to promote muscle plasticity in lower extremity muscles.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies documenting social comparison with respect to coping [27][28][29][30] and especially downward contrast (a positive response to realizing others were worse-off) was reported as particularly related to constructive coping in persons with SCI. 27 'Fighting spirit' (that is, efforts to behave independently) 23 requires that the individuals think they can take control of the situation themselves and 'fight back' to make their lives better.…”
Section: Discussionmentioning
confidence: 99%